Respostas

2014-08-13T21:36:57-03:00
,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,
1 3 1
voce tentou mais mesmo assim obrigada
A melhor resposta!
2014-08-13T21:37:41-03:00
Qual o resultado dessa equaçao      8( P + 1 ) - 3 ( 5 - 2P) = 6 - 2 (P -1)


 8( P + 1 ) - 3 ( 5 - 2P) = 6 - 2 (P -1)

 8(P +  1) - 3(5 - 2P)    =  6 - 2(P- 1) fazer distributiva(multiplicação)
 8P   + 8  - 15  + 6P    =  6 - 2P + 2
8P + 6P + 8 - 15        =  6 + 2 - 2P
      14P  - 7               =     8   - 2P

14P - 7 = 8 - 2P
14P + 2P =8 + 7
       16P  = 15
P = 15/16




2 5 2